Influence of preoperative emotional state on postoperative pain following orthopedic and trauma surgery (Revista Latino-Americana de Enfermagem, 2014)
OBJECTIVES: to analyze the relationship between preoperative emotional state and the prevalence and intensity of postoperative pain and to explore predictors of postoperative pain. METHOD: observational retrospective study undertaken among 127 adult patients of orthopedic and trauma surgery. Postoperative pain was assessed with the verbal numeric scale and with five variables of emotional state: anxiety, sweating, stress, fear, and crying. The Chi-squared test, Student's t test or ANOVA and a multivariate logistic regression analysis were used for the statistical analysis. RESULTS: the prevalence of immediate postoperative pain was 28%. Anxiety was the most common emotional factor (72%) and a predictive risk factor for moderate to severe postoperative pain (OR: 4.60, 95% CI 1.38 to 15.3, p